169 Similar Proportions Return to Work Following Fusion and Decompression Alone for Degenerative Grade 1 Lumbar Spondylolisthesis, Though the Trajectories Differ: An Analysis of the Quality Outcomes Database. Issue Volume 65:Issue CN(2018)Supplement 1 (16th August 2018) - Chan, Andrew K.H; Bisson, Erica F; Bydon, Mohamad; Glassman, Steven D; Foley, Kevin T; Potts, Eric A; Shaffrey, Christopher I; Shaffrey, Mark E; Coric, Domagoj; Wang, Michael Y; Knightly, John J; Park, Paul; et al.
Abstract: INTRODUCTION: Low back pain is a leading cause of work-related disability in the United States and results in significant costs, including up to 20 billion annually due to lost productivity of the gainfully employed. Thus, return to work (RTW) is an important metric in the comparison of fusion versus decompression alone for grade 1 degenerative lumbar spondylolisthesis (DLS). METHODS: This was a retrospective analysis of a prospective registry. A total of 599 patients underwent surgery for grade 1 DLS at 12 high-enrolling sites. Baseline variables were collected. Employment was defined as being employed and actively working or employed and on leave at time of surgery. RTW was assessed at 3 and 12 mo following surgery. RESULTS: At baseline, 264 patients (44.1%) were employed. At baseline, there were a higher proportion of patients in the fusion cohort (219/462; 47.4%) who were employed compared with the decompression alone cohort (45/137; 32.8%; P = .003). At 3 and 12 mo, for patients eligible for RTW, 62.6% and 74.3%, respectively, were able to do so. In a subgroup analysis of the decompression alone cohort, 64.1% demonstrated RTW at 3 mo with a rate that was similar at 12 mo (65.0%) ( P = .94). In the fusion cohort, 62.3% demonstrated RTW at 3 mo with rates that continued to increase at 12 mo (75.8%) ( P = .01). There were no significant differences in RTW between the decompression alone and fusion cohorts at 3 and 12 mo ( P = .83 and P = .30, respectively). CONCLUSION: At 12 mo, the overall RTW rate was equivalent between the decompression and fusion cohorts. The decompression alone cohort reached peak RTW at 3 mo, which remained stable at 12 mo. Though the fusion cohort showed similar RTW at 3 mo, the proportion continued to rise at 12 mo. Further study is required to determine RTW rates in longer follow-up.